2021
DOI: 10.18203/2349-2902.isj20215127
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of routine histology for haemorrhoidectomy specimens

Abstract: Background: Routine histology for haemorrhoidectomy specimens remains commonplace in clinical practice, as a method of detecting incidental anal cancer. However, its utility and cost-effectiveness is unclear in the literature. This study aimed to determine the cost-effectiveness of routine histology for haemorrhoidectomy specimens in a regional Australian hospital. The secondary aim was to determine the proportion of specimens sent for histology, and whether individual surgeons had a statistically significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…found no cases of cancer or AIN among 119 hemorrhoid samples, and Matthysens et al. identified only three malignancies out of 311 specimens, all of which had suspicious macroscopic appearances 9,10 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…found no cases of cancer or AIN among 119 hemorrhoid samples, and Matthysens et al. identified only three malignancies out of 311 specimens, all of which had suspicious macroscopic appearances 9,10 …”
Section: Resultsmentioning
confidence: 99%
“…10 However, Navale et al only found gross abnormalities in 3 out of 54 AIN cases, and Watter et al found no cases of macroscopic dysplasia or neoplasia. 9,16 This suggests that gross abnormalities may not always be evident in specimens harboring neoplasia.…”
Section: Macroscopic Appearancementioning
confidence: 99%